Museus universitários e políticas públicas : gestão, experiências e dilemas na Universidade Federal de Uberlândia, 1986-2010 - Meirelles, Lídia Maria (2015)
The current scenario of museum policies in Brazil results from intense discussions and collective demands. The advances made in the government of Luiz Inácio Lula da Silva, with the institutionalization of structural and legal marks of support and the implementation of public policies within the museum field, do not seem to have produced impacts and changes in practices developed by museums linked to public universities. This study aimed to understand the situation experienced by Federal University of Uberlândia s museums, above all Museu do Índio (Indian museum): its challenges and contradictions in such policies. In light of theoretical conceptions related to heritage, culture, and museum policy, this study aimed to assess whether these museums keep attuned to such indicators. It also relied on references from the fields of history, museum studies, anthropology, and sociology. The research covered a period starting in 1986 when Federal University of Uberlândia created its first museums and ends in 2010 the final year of Luiz Inácio Lula da Silva second government and when museums national policy begun to be implemented. The research relied upon sources such as interviews, minutes of meetings, reports, and newspapers. The thesis presents the course of cultural, heritage, and museum development policies in Brazil to contextualize its perspectives, its setbacks, and its achievements. In addition, it shows hardships experienced by this university museums its impasses and restrictions concerning the institution that houses them and the possibilities of overcoming these obstacles.